Legality of the Legal Status of Kratom Plants in Indonesia - Avridha Riyanti Maharani; Handoyo Prasetyo (UNIFIKASI : Jurnal Ilmu Hukum, 2022)
This research aims to address the following research questions:Â  Why is kratom plant considered illegal in Indonesia? Is there any legal protection for Indonesian farmers who cultivate kratom plants? This study employed normative legal method combining with a qualitative approach. This method relied on secondary data gathered from books, journals, laws, court decisions, and the internet. The information gathered was about kratom plants in Indonesia. In addition, a legal approach was also involved to review selected kratom plant regulation in Indonesia. The study revealed that the legality use of kratom is governed by the circular letter of the Head of the POM No: HK.04.4.42.421.09.16.1740 of 2016, the prohibition on the use of Mitragyna Speciosa (Kratom) in traditional medicines and health supplements. There are numerous side effects for those who consume the kratom plant, according to its content. Since 2013, it has been classified as an NPS (New Psychoactive Substance) and the National Narcotics Agency in an effort to prevent the spread of Kratom plants in Indonesia. Starting with the issuance of a policy, a total ban effective as of 2022. Farmers who cultivate Kratom Plants must switch crops because kratom is classified as Narcoticsâ”€ it cannot be cultivated or traded freely.